Protein homeostasis during ageing: C. elegans as a model organism - Tavernarakis, Nektarios (Henry Stewart Talks, 2013)
Ageing and senescent decline, Protein modifications during ageing, Main cellular protein homeostasis mechanisms, Effects of ageing on protein homeostasis, Regulation of protein synthesis, Linking protein synthesis and ageing